Analisis Pembentukan Kata pada Platform Telegram : Studi Kasus Lowongan Kerja di Daerah Surabaya - Rima Khoirunisa; Tarisha Nailya Dermawan; Dinda Rizky Aulia; Catur Khaila Fillaili; Taswirul Afkar (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study aims to analyze word formation errors found on the Telegram platform, especially in job vacancy announcements in Surabaya. This study focuses on identifying and describing the types of language errors that often appear, such as inappropriate use of capital letters, incorrect writing of loan words, and incorrect use of punctuation. This study uses a qualitative descriptive method with a content analysis approach. Data were collected through screenshots of conversations and job vacancy announcements uploaded in Telegram groups related to job vacancies in Surabaya. The analysis process was carried out through in-depth observation of the data, by identifying error patterns that often appear in job vacancy announcement texts in Telegram groups. The results of the study show that errors in the use of capital letters are the most dominant type of error. Examples include inappropriate placement of capital letters, such as in words that should begin with a lowercase letter or excessive use of capital letters. These errors often reflect a lack of understanding of formal and professional writing rules. In addition, various errors were found in the writing of loan words that do not follow Indonesian language rules. For example, words that come from foreign languages ​​are often written with incorrect spelling or are not adjusted to standard rules. This can reduce the accuracy of the message to be conveyed, especially in formal contexts such as job vacancies. Punctuation errors are also a significant finding in this study. Omission of important punctuation, such as commas and periods, or improper use of punctuation often causes ambiguity in message delivery. As a result, the information conveyed is less clear and can cause misunderstandings for the recipient.